PENGARUH ORGANIZATIONAL JUSTICE, JOB SATISFACTION DAN SUBJECTIVE WELL-BEING TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT TITIS SAMPURNA JAKARTA - I Putu Yoga Sugiastika (2018)
The aim of this study to determine the effect of Organizational justice, Job satisfaction, and Subjective well-being to Organizational citizenship behavior. the hypothesis in this study is Organizational justice, Job satisfaction, and Subjective well-being directly influence positive and significant to Organizational citizenship behavior, meaning that the higher Organizational justice, Job satisfaction, and Subjective well-being perceived by employees the tendency of employees behave OCB higher, and otherwise. The subjects of this study were 63 employees PT Titis Sampurna Jakarta. The sampling technique in this method uses saturated sampling, while data analysis techniques used Partial Least Square (PLS) where the hypothesis is accepted if the P-Values <0.05. the result of the largest path coefficient value is shown by the influence of Job satisfaction on Organizational citizenship behavior of 2,199. Then the second largest is the influence Organizational justice on Organizational citizenship behavior of 2.094, and the smallest is the influence of subjective well-being on organizational citizenship behavior of 2.054. The results of this study indicate that Organizational justice, Job satisfaction, and Subjective wellbeing directly positively and significantly influence the Organizational citizenship behavior, so the conclusion of this hypothesis is accepted